The Impact of Road Infrastructure in Pengkadan Baru Village on Students' School Interest in SMA Negeri 1 Kelam Permai - Pangestu, Dwi Ageng; Harjanti, Diah Trismi; Anasi, Putri Tipa; Apriliyana, Muhammad Iqbal (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
Students' willingness to attend school is greatly affected by the state of the infrastructure, especially the condition of the roads they travel on. Roads play a crucial role in making their journeys to school possible. Ideally, road infrastructure should be both safe and functional. However, at SMA Negeri 1 Kelam Permai, 26 students from the village of Pengkadan Baru face a daily challenge, they must travel on roads that are severely damaged to reach their school. This challenging situation led the researcher to explore how the poor road conditions in Pengkadan Baru affect students’ motivation to attend school. Through quantitative descriptive analysis and involving 26 students from Pengkadan Baru Village as respondents to support this research. The findings show that the road infrastructure in Pengkadan Baru is classified as